A simple method for isolation of rest of trypsinized stem cells with magnetic beads - Sudhir Bhatia (Poltekkes Kemenkes Yogyakarta, 2021)
Till now, there is no laboratory in the world, which makes thoughts that there may be still stem cells remaining in the flasks after the trypsin treatment. The user checks the presence of stem cells during trypsinization with the microscope whether the whole population of stem cells has been collected. Magnetic beads are being used around the world to isolate different kinds of cells like CD4, CD8, CD34, and other cells. One of the advantages of magnetic isolation is that they can be used to isolate cells from solutions containing even a low number of targeted cells. We conducted the experiments to see whether all remaining MSC can be obtained from a trypsin-treated flask with magnetic beads isolation.